Stakeholders' perceptions of policy options to support the integration of community health workers in health systems - Onyema Ajuebor; Giorgio Cometto; Mathieu Boniol; Elie A. Akl (BMC, 2019)
Abstract Background Community health workers (CHWs) are an important component of the health workforce in many countries. The World Health Organization (WHO) has developed a guideline to support the integration of CHWs into health systems. This study assesses stakeholders' valuation of outcomes of interest, acceptability and feasibility of policy options considered for the CHW guideline development. Methods A cross-sectional mixed methods (quantitative and qualitative) study targeting stakeholders involved directly or indirectly in country implementation of CHW programmes was conducted in 2017. Data was collected from 96 stakeholders from five WHO regions using an online questionnaire. A Likert scale (1 to 9) was used to grade participants' assessments of the outcomes of interest, and the acceptability and feasibility of policy options were considered. Results All outcomes of interest were considered by at least 90% of participants as 'important' or 'critical'. Most critical outcomes were 'improved quality of CHW health services' and 'increased health service coverage' (91.5% and 86.2% participants judging them as 'critical' respectively). Out of 40 policy options, 35 were considered as 'definitely acceptable' and 36 'definitely feasible' by most participants. The least acceptable option (37% of participants rating 'definitely not acceptable') was the selection of candidates based on age. The least feasible option (29% of participants rating 'definitely not feasible') was the selection of CHWs with a minimum of secondary education. Conclusion Outcomes of interest and policy options proposed were rated highly by most stakeholders. This finding helps to reinforce their usefulness in meeting the expectations of the CHW guideline end-users to properly integrate CHWs into health systems.